The Role and Development of the Function of ABRI (Angkatan Bersenjata Republik Indonesia) in the New Order Period - Ali Ginanjar Inpantri; Muhammad Ikbaarshaff Hasabi Siddiq; Maya Putri Jayanti; Muhammad Ihsan Alhabsy (GoResearch - Research & Publishing House, 2022)
During the New Order era, the dual function of ABRI was used as a defense and security force and had the function of socio-political power which then had very important values ​​in realizing national stability. This research was carried out so that later it could become literature that could be known and known to us and others, by examining the history of the dual function of ABRI, the development of the dual function of ABRI, and the implementation of ABRI's role in the socio-political field. Then ABRI had a role in socio-political power in 1966-1997 with stabilizers, dynamists, and pioneers as well as being the main field in the implementation of a liberal democratic system, under the pretext of